2016
DOI: 10.1080/03079457.2016.1168513
|View full text |Cite
|
Sign up to set email alerts
|

Selected clinical chemistry analytes correlate with the pathogenesis of inclusion body hepatitis experimentally induced by fowl aviadenoviruses

Abstract: In the present study, clinical chemistry was applied to assess the pathogenesis and progression of experimentally induced inclusion body hepatitis (IBH). For this, five fowl aviadenovirus (FAdV) strains from recent IBH field outbreaks were used to orally inoculate different groups of day-old specific pathogen-free chickens, which were weighed, sampled and examined during necropsy by sequential killing. Mortalities of 50% and 30% were recorded in two groups between 6 and 9 days post-infection (dpi), along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
4
10
0
2
Order By: Relevance
“…Contact birds were probably infected by the oral route from the contaminated faeces of the inoculated chickens. In other trials, horizontal transmission of different FAdV serotypes (including 8b and 11) was also achieved (Mendelson et al, 1995;Ono et al, 2007;Matos et al, 2016b). In our study, shedding results correlated with the administered dose; that is, birds infected with the higher viral dose excreted the virus at a higher concentration, and birds in contact with them started to excrete the virus earlier than the ones infected with a low dose.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Contact birds were probably infected by the oral route from the contaminated faeces of the inoculated chickens. In other trials, horizontal transmission of different FAdV serotypes (including 8b and 11) was also achieved (Mendelson et al, 1995;Ono et al, 2007;Matos et al, 2016b). In our study, shedding results correlated with the administered dose; that is, birds infected with the higher viral dose excreted the virus at a higher concentration, and birds in contact with them started to excrete the virus earlier than the ones infected with a low dose.…”
Section: Discussionsupporting
confidence: 69%
“…While some studies (Dar et al, 2012;Zhao et al, 2015, Matos et al, 2016a obtained moderate to severe clinical signs and mortalities when infecting chickens at different ages (from 1 day to 3 weeks of age) with FAdV serotypes 8b and 11, Grgic and colleagues (2011) could reproduce neither clinical signs nor mortality after infecting 10-day-old birds with an FAdV serotype 8 strain. Moreover, in a recently published trial (Matos et al, 2016b), birds infected with FAdV-8b and FAdV-11 showed more severe clinical signs and mortalities than those inoculated with FAdV serotypes 2, 7 and 8a.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, increasing clinical cases of FAdV infections have been concerned and many FAdV strains related to IBH have been identified in many countries [ 11 , 15 , 25 , 33 , 38 – 43 ]. Some of them were highly pathogenic to chickens and were associated to considerable economic losses [ 15 , 26 , 33 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant FAdV-E strains addressed in this study were isolated from IBH outbreaks, or induced disease in experimental settings [70], underlining their clinical relevance. Antigenic segments with parental origin of types -6 and -7, which are usually not linked to IBH, were also found among field isolates (12-10101, 09-8330, and 13-19395), although experimental data on the pathogenicity of the latter two strains are unavailable so far.…”
Section: Discussionmentioning
confidence: 99%